Examination of the Form and Content of “Semantics”, with a Contrastive Criticism Approach to the Translation - Yusuf Nazari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Ilmud-dilalah” (Semantics) by Ahmad Mukhtar Omar is among the books translated into Persian by Seyyed Hossein Seyyedi, a faculty member of Mashhad University. Considerable usage of the main and original research sources by the writer, and his command of the record of studies done in semantics in the Muslims’ old linguistic heritage have given the book a special position in the semantic studies, which makes its translation necessary.  The cover design, typography, page layout, punctuations, and typographical errors of the translated book were considered in the examination of the form. Examination of the content of the translation focused on the faithfulness in translation of all parts of the book, faithfulness in full translation of the text, faithfulness in conveying the content, specialized terms, literal translation, explanatory footnotes, and the citation style. In this translation criticism which is based on a contrastive attitude, two categories of the options and limitations of the translator were examined, but the focus was more on the limitations. Examinations showed that the translation was done so hastily, and in practice just little scientific and literary revisions were done on it. It has caused a number of errors and shortcomings in this translation to be greater than the number of its advantages, and many parts of the book need to be translated again.